Prinsip Kesopanan dalam Tindak Tutur Remaja Desa Pagedangan Kecamatan Pasar Kemis - Wihaja, Irpa Anggriani; Fitriani, Hamdah Siti Hamsanah (Jurnal Artikula, 2022)
The purpose of this study was to examine the principle of politeness in the speech acts of adolescents in Pagedangan Village, Pasar Kemis sub-district. The background of this research is to show whether the youth's speech contains politeness maxims or not, because usually the language used by children today is not effective and does not attach importance to the politeness element in it. The object of this research is in the form of utterances or conversations carried out by teenagers in Pagedangan Village, Pasar Kemis District. This research method uses a qualitative descriptive method. The research procedure used data collection techniques in the form of audio recording techniques, listening techniques, note-taking techniques, and documentation techniques. Based on the research that has been done, the researchers found that there were maxims that were violated by the teenagers. When the discussion was carried out, the maxim that often appeared was the maxim of compatibility and the maxim that rarely appeared was the maxim of sympathy. In speech events at Karang Taruna meetings, speech acts are often encountered which reflect impoliteness in Indonesian. The theory of politeness principles with various maxims gives speeches on how to speak politely and politely